Optimizing the application of potassium sulfate fertilizer based on the variation in soil mineral accumulation and tobacco growth: a 10-year field experiment - Yu, Keke; Zhang, Zhenwang; Liu, Tao; Fu, Huijie; Lv, Penghui; Zhang, Zhe; Cong, Ping; Zhan, Huaixu; Tang, Lina; Li, Zhiyuan; Dong, Jianxin (Frontiers in Plant Science, 2026)
Potassium (K) is an essential element in tobacco production, especially in Shandong, the main tobacco-growing province in China, where the improvement of tobacco yield and quality is limited by soil K deficiency, thus potassium sulfate (K2SO4) fertilizer is popularly applied by farmers. However, it is unknown how soil physicochemical characteristics and tobacco growth respond to the utilization of K2SO4 fertilizer in the long term. This study aimed to determine the optimal application amount of K2SO4 fertilizer to improve soil health and enhance tobacco leaf K content without yield loss. Four treatments were tested, namely mixes of 82.5 kg a.i. ha −1 K2O + 66.0 kg a.i. ha −1 sulfur (K82.5 + S66), 165.0 + 95.7 (K165 + S95.7), 247.5 + 125.4 (K247.5 + S125.4) and no fertilizer (CK). Excessive use of K2SO4 fertilizer led to soil acidification and a significant decrease in arylsulfatase activity. Soil available potassium (AK) and pH, that exhibited diverse responses over course of 10 years, increased and decreased with the amount of K2SO4 fertilizer applied, respectively. Moreover, the K content in tobacco plants significantly increased after K2SO4 fertilizer application, with that in tobacco leaves being 162.3% and 45.2% higher than that in tobacco roots and stems, respectively. Soil AK exhibited a significant positive correlation with the K content in tobacco roots, stems, and leaves, while soil pH showed the opposite performance. Soil pH is a pivotal factor influencing soil physicochemical characteristics, total dry matter and the K content in tobacco tissue. The application of K165 + S95.7 was more reasonable and economical in terms of matter accumulation. We concluded that the optimal application rate in Shandong was K165 + S95.7, which not only improved soil health and tobacco leaf K content but also reduced input without causing yield loss.